Security behaviour of mobile financial service users. (29th June 2020) - Dzidzah, Esther; Owusu Kwateng, Kwame; Asante, Benjamin Kofi
Abstract : Purpose: The inception of mobile financial services (MFSs) has positively provoked economic growth and productivity, nonetheless, it has pessimistically caused an upward surge in cybersecurity threat. Customers are progressively becoming conscious of some of the threat and several of them now shun away from some suspicious activities over the internet as a form of protection. This study aims to explore the factors that influence users' to adopt security behaviour. Design/methodology/approach: A synthesis of theories – Self-efficacy and technology threat avoidance theories – was used to examine the security behaviour of users of MFSs. Data was gathered from 530 students in Ghana using convenience sampling technique. Data analysis was carried out using descriptive statistics, inferential statistics and structural equation model. Findings: Outcome of the investigation indicate that both mastery experience and verbal persuasion have substantial effect on the avoidance motivation of MFSs users. It was, however, found that emotional state and vicarious experience of users do not influence their avoidance motivation. Also, it was established that avoidance motivation is a positive prognosticator of avoidance behaviour. Practical implications: Understanding the security behaviour of MFS users will help the operators to outline strategies to sustain the successes achieved. Originality/value: Studies on user security behaviour are rare, especially in sub Saharan Africa, thus, this study will contribute to extant literature by adding a new dimension of user security behaviour.